Analysis of School Culture and Governance at SMPN 7 Tarakan: Practices, Habits, and Management - Ibrahim, Sarah; Rafiqa, Syarifa; Asmauliah, Asmauliah (Borneo Journal of English Language Education, 2024)
This research analyses school culture and governance in SMPN 7 Tarakan and the practices, habits, and management that create a conducive learning atmosphere. It underlines the importance of school policies, engagement in co-curricular and extra-curricular activities, a healthy learning environment, and facilities management for students to be engaged and succeed academically. Adopting a qualitative approach based on observational data, the authors establish a link between orderly school rules and disciplinary and structural order but suggest that ethnically diverse communities may benefit from looser structures. The study emphasises the need for sufficient facilities to boost student motivation and engagement in academic and extra-curricular activities. In conclusion, this study offers a possibility to view the school within quality education and students' personal growth by having an integrative perspective — defining a concept of doing justice for educational quality.